DIET ATEROGENIK PADA TIKUS PUTIH (Rattus novergicus strain Wistar) SEBAGAI MODEL HEWAN ATEROSKLEROSIS - Murwani, Sri; Ali, Mulyohadi; Muliartha, Ketut (Jurnal Kedokteran Brawijaya, 2006)
Atherosclerosis is still a major health problem, because 20% of death in the world is caused by atherosclerosis diseases like stroke and myocardial infarct. One of animal models that was successful in atherosclerosis research was New Zealand white rabbit. The purpose of this preliminary research was to determine the atherogenic diet ofwhite rats (Rattus novergicus strain Wistar) as animal model of atherosclerosis especially to find fixed composition and time of the atherogenic diet taken.This research used male; 2 months age, 150-200 grams body weight of white rats Rattus novergicus strain Wistar. The rats were divided into5 groups in equal number, 4 rats respectively. Theywere a negative control group without diet treatment and 4 groups as treatment groups which were given hipercholesterol diet. Atherogenic diet composed of PAR-S, wheat flour, cholesterol, cholic acid, pork oil and water. Data were obtained by measuring of blood cholesterol level and foam cell formation.